A novel gradient negative stiffness honeycomb for recoverable energy absorption. (15th June 2021) - Chen, Shuai; Tan, Xiaojun; Hu, Jiqiang; Zhu, Shaowei; Wang, Bing; Wang, Lianchao; Jin, Yang; Wu, Linzhi
Abstract: This paper designs a novel reusable gradient negative stiffness (GNS) honeycomb structure and focuses on investigating its energy absorption (EA). Contrary to classical normal negative stiffness (NNS) honeycomb structures, the GNS honeycomb is characterized in that its unit cells have regular geometric (stiffness) changes throughout the honeycomb panel. The quasi-static mechanical characteristics of the novel GNS honeycomb are investigated with a combination of experiments and simulations. The influence of the structural parameters on energy absorption is revealed using an experimentally verified numerical model. After that, the repeatability of this honeycomb is verified by cyclic compression. In addition, the vibration control effect of the honeycomb is studied through vibration isolation tests, and revealing that the presented GNS honeycomb has better vibration control performance than the NNS honeycomb. Finally, plate-impact experiments are also performed to investigate the cushion properties of NNS and GNS honeycombs. The test results show that the novel GNS honeycomb has better cushion performance than the NNS honeycomb by inhibiting the threshold of acceleration response amplitude, which again verifies the potential of the novel GNS honeycomb in the EA field.